Multi-point coupling for tool point receptance prediction. (July 2019) - Schmitz, Tony; Honeycutt, Andrew; Gomez, Michael; Stokes, Michael; Betters, Emma
Abstract: This paper describes a multi-point receptance coupling substructure analysis (RCSA) technique for tool point receptance prediction. The portion of the tool inside the holder is coupled to the portion of the holder that clamps the tool at multiple points along the insertion length. The coupling can be rigid or flexible-damped. The procedure is described analytically and then experimental results are presented. The tool point receptances, or frequency response functions, for four carbide tool blank diameters are tested at multiple extension lengths and compared to predictions for an ER32 collet connection. Stiffness matrices are identified for each of the tool blank diameters and reported. Given the predicted tool point receptances, milling process models can be used to select optimized operating parameters at the process planning stage.